Incremental architectures for a permanent human lunar outpost with focus on isru technologies. - Gatto G.; Levrino L.; Gargioli E.; Hall S.; Hoffman J.; Wellons J.; MAGGIORE, Paolo; VIOLA, Nicole; VISCIO, MARIA ANTONIETTA (2014)
Long-term strategic plans for future human space exploration are based on the idea of following an evolutionary path, as this is fundamental to reduce risks and costs associated to deep space missions, as well as to allow testing and validation of critical technologies required for ultimate goals, such as human Mars missions. In this context, in addition to its utility as a precursor for Mars expeditions, extended lunar exploration is of interest in itself, especially since the surface of the Moon is very rich in resources, but it has not so much been explored in-situ. Extended lunar operations may eventually require the establishment of a human lunar outpost. Determining what technologies will be required to accomplish this goal is the motivation for our research. The present paper outlines the conceptual design of a permanent human Moon outpost located at the lunar south pole, defining the main requirements and presenting the arisen system architecture highlighting the incremental steps needed to achieve full operational capability. Particular attention has been given to the design of the base main elements, especially incorporating In-Situ Resource Utilization (ISRU) technologies as a paramount brick of the overall design process. Estimates regard the crew size and the related life support systems, and chiefly the ISRU plants production rate needed to allow the primary lunar base self-support. Moreover, ISRU is considered not only as an enabling factor for affordable human long-term presence on the Moon, but also as an opportunity to provide spacecraft travelling to the Red Planet with propellant, thus reducing their launch mass: calculations are made considering refueling at the Earth-Moon libration point L1, where liquid oxygen tanks would be delivered from the lunar surface. Oxygen extraction through ilmenite reduction is the main technology considered for dimensioning ISRU plants. Another precious resource could be found in sunless cold trap craters at the Moon's south polar region. However, ground truth ...